Amino Acids Brown Oil during Frying - MORIYA, Masafumi; TOTANI, Nagao; TAKADA, Mitsunobu; KUZUME, Tika; YAMAGUCHI, Ayako (Journal of Oleo Science, 2006)
We previously reported that 50% of the browning of frying oil in food manufacturing was due to thermal deterioration of the oil itself and the rest was most probably due to reactions involving amino acids in juice exuded from frying foodstuffs. The purpose of this study was to demonstrate that amino acids are released in 20 h from foodstuffs into oil heated at 180°C in an amount sufficient to brown the oil to Gardner color (G)>10. The amount of juice exuded during deep-frying of foods was determined, and then heating conditions in a microwave oven that exude the same amount of juice from foodstuffs as in deep-frying were chosen. Juice thus prepared was defatted, and substances of molecular weights (MW) over 3000 were centrifuged out through a membrane filter. Free amino acids in the filtrate were quantified by HPLC. With the obtained amino acid contents of foodstuffs, it was calculated that some kilograms of pork, beef, or chicken, or some hundreds of grams of shrimp or scallops would exude enough amino acids to brown 1 L oil to G>10 at 180°C in 20 h. Next, fresh virgin oil was heated at 180°C for 20 h with powder prepared from the juice by freeze-drying. The color scores of oil (1 L) with added powder from about 1 kg or more of pork or chicken reached G>10. This finding means that amino acids exuded from amounts of pork or chicken easily possible to fry in practice without addition of fresh oil were sufficient to cause browning. It was demonstrated that amino acids exuded from frying foodstuffs were responsible for frying oil browning, regardless of batter coatings on the foodstuffs.